Handbook of good psychiatric management for adolescents with borderline personality disorder - Choi-Kain, Lois W.; Sharp, Carla (American Psychiatric Association Publishing, 2022)
"Handbook of Good Psychiatric Management for Adolescents With Borderline Personality Disorder uses good psychiatric management for adolescents to demystify borderline personality disorder in young people. The book describes common problems that arise during each phase or aspect of treatment, from patient rejection of diagnosis and conflicts among clinicians providing care to nonadherence to medications and concerns about stigma. The pragmatic principles outlined in this book are based on real-world experience and bolstered by scientific evidence and provide a road map to provide "good enough" care even in the absence of specialized treatments"--